Characterization of the Process of Attention to Hypertensive People in a Cerro Municipality Polyclinic - Marilyn Hernández Sánchez; Addys Díaz Piñera; Armando Rodríguez Salvá; Mayté Más Gómez; Hortensia Cueto Lamar (Revista Finlay)
Foundation: to achieve adequate control of arterial hypertension, it is essential to identify the gaps that threaten the quality of the care process, an aspect that constitutes a challenge for the National Public Health System. Objective: to characterize the management of hypertensive patients at the Héroes of Girón Polyclinic in the Cerro municipality in 2022. Method: a descriptive cross-sectional study was carried out in 363 people aged 35 years and older classified as hypertensive. A questionnaire was applied to them about aspects related to the process of care for hypertensive patients. Blood pressure measurements were performed at three different times. The following variables were analyzed: sociodemographic, risk factors, access to health services, consultation follow-up, treatment, BP control. Descriptive statistics were applied to analyze the data and present the results. Results: hypertensive people over 60 years of age, female, accompanied, with high school education and retired occupation predominated. The most frequent comorbidities were: diabetes mellitus (22.8 %), hypercholesterolemia (17.6 %) and obesity (15.4 %). 68.8 % of these people did not feel the need for care in the last year and only 29.4 % were seen in a follow-up consultation. 30.0 % of patients had not had their blood pressure measured for more than a year, 99.1 % had indicated treatment, 50.9 % were controlled and 59.5 % adhered to treatment. Conclusions: the care these people received is not correct. There were difficulties with dispensing, compliance with the program, in addition to a low perception of risk in these people.